An analysis on the suitability of selected newspaper material as a teaching resource in efl courses - Diez, Carolina (2010)
The “Universidad Técnica Particular de Loja” as a requirement to the students who have finished the four years of preparation to get the Bachelor’s Degree in EFL teaching asked their students to carry out a research project about “The suitability of newspaper material as a teaching resource in EFL courses”, to know if this type of material can be useful as a resource to work with in the English classroom to teach or practice using three variables: Grammar, Vocabulary and Reading Strategies. As the totality of the schools in Guayaquil employ a course book; newspaper material can be perfectly used as a complement to teach any of the three variables in a different, motivating way as the newspaper can provide real and current issues, interesting vocabulary, varied topics, etc.